PSIKOEDUKASI UNTUK MENINGKATKAN PEMAHAMAN MENGENAI KECEMASAN DAN SOLUSINYA PADA UMKM di Kota X - Linda Wati; Heryanti Satyadi; Cynthia Sutanto (PROSIDING SERINA, 2021)
Anxiety is one of the psychological problems that every individual has. This is because since birth the individual already has trait anxiety. The pandemic condition makes individuals experience state anxiety with sudden changes that have an impact on the economic conditions of the families who open micro, small and medium enterprises. Individuals who experience anxiety problems usually feel trembling, cold sweats, muscle tension, headaches, irritability, insomnia, chest palpitations, feeling tired to shortness of breath. The pandemic condition poses challenges for every individual. This makes the individual feel pressure that causes a physical reaction. When faced with this, many individuals do self-diagnosis with online applications so that sometimes it makes individuals even more anxious. The purpose of psychoeducational activities carried out is to provide counseling about anxiety, types of anxiety and solutions to manage anxiety that is owned by each individual. The results of psychoeducation provide an overview to individuals regarding the appropriate solutions to manage their anxiety and the most appropriate solutions that can make participants feel comfortable. Participants felt that the Safe Place technique where they imagined a comfortable place for themselves was a technique that made participants feel calmer.